Right of women to obtain divorce under Shariah and Islamic family law of Malaysia: some emerging issues - Abdul Hak, Nora (2012)
Introduction: Islam takes a realistic view of human affairs and therefore, it attaches great importance to the happiness of both the spouses in Marriage. It provides that every attempt should be made to preserve a marriage, but once it is established that marriage has broken down (shiqaq), Islam does not scruple to allow the parties to separate from each other. Talaq (divorce) is pennitted in Islam, but it is, as mentioned by Prophet Muhammad s.a.w, the most abominable of all legitimate acts. Divorce does not generate merit therefore, it should be prevented from taking place. In Islam, marriage is expected to last until one of the spouses dies. However, if the spouses cannot live together any more in peace and harmony in the marital relationship, then its continuance is no longer considered desirable. In other words, divorce is pennitted as a matter of necessity for the avoidance of greater evil which may result from the continuance of a marriage. The failure of marriage can be due to many reasons. It may also be due to certain defects or faults in one or both of the spouses which give the right to apply for ta'liq or fasakh. In Islam, when the wife's conduct is undesirable such as, nusyuz to her husband, the husband is permitted to divorce her. When the husband becomes a transgressor, for example, the husband incapable of maintaining the wife or he ill-treats the wife, Islam also grants women the right to dissolve a marriage through khulu' ,fasakh and ta'liq. It is stated in the Qur'an that: "And women have rights similar to those against them in a just manner". This verse shows that men and women have similar rights and obligations against one another. For that reason, Islam provides some grounds for women to obtain divorce. This paper will briefly describe the concept of divorce i.e., ta'liq, khulu' and fasakh in Islam. It also explains the law and the procedures as provided under the Islamic Family Law in Malaysia for the women to exercise this right of divorce by highlighting some of the emerging issues in practice at the Syariah Court.